2003
DOI: 10.1086/378692
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Differences in theChlamydia pneumoniae tyrP Locus Related to Vascular Tropism and Pathogenicity

Abstract: Chlamydia pneumoniae is an obligate intracellular pathogen that causes respiratory infections and has been associated with cardiovascular disease. We compared respiratory and cardiovascular isolates to find genetic differences associated with pathogenicity. A polymorphic region encoding a tyrosine/tryptophan permease was found to differ between disease isolates. Respiratory strains contained multiple copies of the tyrP gene, and vascular strains contained a single copy. Single-nucleotide polymorphism analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 26 publications
1
37
1
Order By: Relevance
“…6). This finding is consistent with the observations in other bacteria that a large molar excess of the corepressor, L-tryptophan, is necessary for negative regulation by TrpR (10,38). We also tested other representative amino acids but found that neither L-tyrosine, Lphenylalanine, L-alanine, L-arginine, L-serine, L-methionine, nor L-proline could function as a corepressor for TrpR (data not shown).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…6). This finding is consistent with the observations in other bacteria that a large molar excess of the corepressor, L-tryptophan, is necessary for negative regulation by TrpR (10,38). We also tested other representative amino acids but found that neither L-tyrosine, Lphenylalanine, L-alanine, L-arginine, L-serine, L-methionine, nor L-proline could function as a corepressor for TrpR (data not shown).…”
Section: Resultssupporting
confidence: 92%
“…The mtr homolog is called tyrP, and it is predicted to encode a tyrosine/tryptophan transporter. There has been particular interest in tyrP because the number of gene copies in C. pneumoniae has been shown to vary according to tissue tropism and disease manifestation (10). So far, however, there is little evidence to indicate that any of these genes are regulated by TrpR in Chlamydia.…”
Section: Discussionmentioning
confidence: 99%
“…Tryptophan has been shown to play a pivotal role in chlamydial pathogenesis, and tryptophan limitation induces chlamydiae to enter a persistent growth state (reviewed in reference 18). As another example, strain variation in the tyrP tyrosine/tryptophan permease has been shown to correlate with C. pneumoniae tissue tropism (5). The finding that arginine-dependent regulation is present in only a subset of Chlamydia species suggests that the role of this essential amino acid in species-specific differences in tissue tropism and pathogenesis deserves a closer look.…”
Section: Discussionmentioning
confidence: 99%
“…A phylogenetic tree (data not shown) indicates that a gene duplication occurred in the common ancestor of C. trachomatis and C. muridarum. Gieffers et al (40) noted that respiratory strains of Cp. pneumoniae (e.g., strains CW and AR) possessed two paralogous copies of tyrP, whereas vascular strains (e.g., strains J and T) had a single tyrP gene.…”
Section: Self-limitation Of Trp Import Caused By Trp Starvationmentioning
confidence: 99%
“…pneumoniae. It is interesting to consider that whereas the expression of two TyrP paralogs should promote increased competence for Trp import during Trp sufficiency (and this has indeed been shown [40]), it also would increase the Trp burden during Trp insufficiency.…”
Section: Self-limitation Of Trp Import Caused By Trp Starvationmentioning
confidence: 99%